Kerangka Teoritik Untuk Mengukur Tingkat Kapasitas Masyarakat dalam Pembangunan Obyek Wisata - Sunardi Purwaatmoko (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract: Investment of people capacity in local community seems tobe essential for the advancement of tourism development. The income growth of the local community depends on the extent of cappacity achieved by the local community. The more powerful the local community is, the more capable the local community to exploit the arrival of vissitors. Viewed from community building approach, the fisical develomment of tourism destination should be precided by building internal capacity of the local communitywhich includes various dimensions: community leadership, community participation, the communitystructure, skill and knowledges, resourse mobillisation and the power of community and external supports. Keywords: community, capacity, development